Odontogenic myxoma of posterior maxilla – A rare case report - Soundarya Ramesh; Poornima Govindraju; Balaji Pachipalusu (Journal of Family Medicine and Primary Care, 2020)
Odontogenic myxoma is a benign, rare neoplasm of mesenchymal origin comprising of 3%–6% of all odontogenic tumors. Odontogenic myxoma occurs more commonly in the second and third decade and is more commonly seen in mandible compared with maxilla but behaves more aggressively in maxilla as it spreads through the maxillary antrum. It is usually associated with a painless swelling without any symptoms. The radiographic features are similar to other odontogenic tumors, and hence, it leads to diagnostic dilemma. Therefore, thorough knowledge regarding clinical, radiographical, and histopathological features are important to arrive at a proper treatment protocol as it shows a high recurrence rate. The aim of this paper was to present a rare case of 21-year-old male with a chief complaint of swelling in the left maxilla that infiltrated the maxillary sinus in a very short duration.